Directing My Life Fiction Film Using Mise En Scene Implementation to Realise Realism Style - Pratama, Ferli Mulianto; Rustim; Abidin, Zainal (Kirana Publisher (KNPub), 2025)
The fictional film My life tells the story of a young child forced to work due to economic hardship. Through this narrative, the filmmakers aim to convey an important lesson to the audience: children, especially those underage, should not be subjected to labour. The film adopts a Realist style of direction to enhance its portrayal, ensuring that the narrative feels as authentic and true to life as possible. The Realist approach focuses on presenting reality as it is, minimising artistic manipulation to maintain the integrity of the events depicted. This approach is reinforced by the mise en scene, a key element under the director's responsibility. Mise en scene encompasses all visual components within the frame, such as acting, costumes, settings, makeup, and the performance of the actors. Through this, My life serves as both an artistic piece and a social commentary, highlighting the harsh realities of child labour while urging reflection on societal issues. The film's direction emphasises realism by capturing the emotional and physical truths of the characters' experiences, making it a poignant portrayal of the struggles faced by underprivileged children in Indonesia.